COVID-19 Awareness, Vaccination, and Health Outcomes: A Comparative Study of Residents of Western Libya and Libyan Expatriates in the United Arab Emirates (Derna Academy Journal for Applied Sciences, 2024)
The COVID-19 pandemic has had varying impacts across nations, influenced by differences in healthcare infrastructure, governance, and public awareness. Libya and the United Arab Emirates (UAE) exemplify two contrasting contexts in managing the crisis. This study aimed to assess awareness, perceptions, and practices related to COVID-19 among Libyan residents in western Libya and Libyan expatriates living in the UAE, with a particular focus on infection control behaviors, vaccination acceptance, and healthcare response. A cross-sectional comparative study was conducted, including 150 participants from western Libya and 150 Libyan expatriates in the UAE. Data were collected using structured questionnaires and complemented with official health reports and published studies. Descriptive and comparative analyses were carried out using SPSS version 23 to evaluate differences in awareness levels, preventive practices, and health outcomes between both groups.  The findings revealed significant disparities between the two populations. Libyan residents exhibited limited awareness and lower compliance with preventive measures, resulting in lower vaccination acceptance and higher incidence of severe COVID-19 complications such as respiratory distress and mortality. Conversely, Libyan expatriates in the UAE demonstrated higher awareness, adherence to infection control practices, and a strong willingness to receive vaccines, leading to milder disease outcomes. These differences can be attributed to variations in healthcare accessibility, public health communication, and the efficiency of vaccination campaigns. In conclusion, public awareness, accessible healthcare, and proactive vaccination initiatives are essential in mitigating the effects of pandemics. Libya could benefit greatly by adopting lessons from the UAE’s experience, emphasizing health education, vaccine advocacy, and improved healthcare system preparedness.